The Implementation of Hypnobirthing Effect on Pain Relief in the Intrapartum Period at Klinik Pratama Rakyat Hospital Makassar (Medico Legal Update, 2021)
The pain of childbirth is one of the factors that causes a mother to become anxious even to the point ofdespair, so mothers tend to choose a shortcut to speed up their childbirth, either by requesting an operation,or by taking a remedy to relieve the pain by taking an analgesic drug, whereas pain caused during childbirthis pathological because of the effects of changing uterus that creates pathways or openings.The type of research is experimental quantitative research using Quasi Experimental method, namelyexperimental design with the observation design (measurement pain intensity) before and after treatment(Hypnobirthing treatment) which consists of the two group, namely the intervention group (Hypnobiththing)and the control group. Sampling was taken from June to August 2020 with the number of samplingsintervention group (Hypnobiththing) as many as 20 respondents and the control group as 20 respondents.Data analysis method uses Univariate and Bivariate with t-test using SPSS Computer Program.The results were obtained with the average of pain intensity in childbirth after being given Hypnobiththinghada decrease in pain while the control class was upgraded. The results of statistical test are presented ? valuaby 0.000 at the mistaken rate of (?) 5% or 0,05 (trust 95%) so value is ? < ?. The data indicated that therewas a significant (apparent) of Hypnobiththingtreatment in childbirth relief. The conclusion of this researchwas that there was a significant Hypnobiththing effect on the treatment of childbirth at KlinikPratama RakyatHospital. That was expected for midwife duty at KlinikPratama Rakyat Hospital to adopt the method ofHypnobirthing to assist the mothers with normal childbirth.